DIRECTIONS OF CONTROL IN THE SPHERE OF URBAN PLANNING ACTIVITIES (Bulletin of criminological association of Ukraine, 2025)
It is noted that one of the key areas of control in the field of urban planning is ensuring that the subjects of the latter comply with the norms of the legislation, which includes the implementation of subjective obligations, technical and other standards, rules and requirements for the implementation of relevant processes and works, etc. Not only the correctness and completeness of the implementation of legislative provisions is monitored, but also the fact of their compliance in general, which allows to prevent situations of clearly illegal activity, for example, construction in an unspecified place, neglect of the requirements for the protection of cultural heritage, and so on. It is emphasized that control during the implementation of urban planning activities is aimed not only at verifying compliance with the provisions of the legislation and technical norms, but also at ensuring the inviolability of key human rights and freedoms. The implementation of processes in the field of urban planning must meet general social interests, not create obstacles to the normal use by each person of their constitutional powers, and so on. It is noted that systematic and comprehensive control over the preparation for the construction of relevant architectural and other objects, as well as the subsequent process of implementing construction works, is a guarantee of the correctness and safety of the latter, the compliance of each of their stages with all technical and legal requirements.
Keywords: control; urban planning; urban planning activity; areas of control